Barrier Effect of a New Topical Agent on Damaged Esophageal Mucosa: Experimental Study on an ex vivo Swine Model - Salaroli R (Clinical and Experimental Gastroenterology, 2020)
Roberta Salaroli,1 Domenico Ventrella,1 Chiara Bernardini,1 Alberto Elmi,1 Augusta Zannoni,1,2 Maria Laura Bacci,1,2 Monica Forni,1,2 Fiorella Calanni,3 Antonella Ferrieri,4 Fabio Baldi5 1Department of Veterinary Medical Science, University of Bologna, Ozzano Emilia, Bologna, Italy; 2Health Sciences and Technologies Interdepartmental Center for Industrial Research, University of Bologna, Bologna, Italy; 3Pre-Clinical Research Department, Alfasigma, Bologna, Italy; 4Division of Clinical Research, Department of Research and Development, Alfasigma, Bologna, Italy; 5Center for the Study of Diseases of the Esophagus, University of Bologna and Gruppo Villa Maria Care & Research, Ravenna, ItalyCorrespondence: Monica ForniDepartment of Veterinary Medical Science, University of Bologna, Via Tolara, 50, Ozzano Emilia 40064, Bologna, ItalyTel +39 051 20 9 7913Email monica.forni@unibo.itPurpose: AL2106 is a new medical device based on a mixture of chondroitin sulphate in a xyloglucan and glycerol solution made to maximize its bioadhesive capability to the esophageal mucosa. The aim of the present study was twofold to evaluate the AL2106 protective effect on the esophageal mucosa when exposed to an acidic solution mimicking gastric reflux and to assess the resilience of this effect to saline washing.Materials and Methods: A porcine ex vivo model was used and the effects of the new medical device were compared to a sodium alginate suspension (SAS) already present on the market which was assumed as reference. Mucosal damage was induced in 19 porcine esophagi by perfusion with an acidic solution added with pepsin, and Evans blue dye (EBD) tissue uptake was used as an indicator of mucosal permeability. The EBD penetration, expressed as EBD μg/g of dry tissue, was assessed in specimens of untreated damaged mucosa and in specimens treated with AL2106 or SAS. The same evaluation was carried out after washing with normal saline.Results: Both topical agents tested significantly reduced the EBD uptake by more than 60% (AL2106 8.4± 4.5, SAS 3.6± 2.7 vs control 23.2± 13.1, p< 0.01). The saline washing did not cause any significant reduction in the protective effect of AL2106 (8.6± 5.9), while it significantly reduced that of SAS (5.9± 4.3, p< 0.05).Conclusion: The new AL2106 medical device showed a good barrier effect against a reflux-like damaging solution and preserved this effect after the mucosal washing test, thus suggesting its possible relevance for the treatment of gastroesophageal reflux disease.Keywords: bioadhesion, Evans blue dye, EBD, animal model, esophagus, gastroesophageal reflux disease, GERD